Patient, Provider, and System Factors Associated With Failure to Follow-Up Elevated Glucose Results in Patients Without Diagnosed Diabetes. (17th August 2017) - Bowen, Michael E.; Merchant, Zahra; Abdullah, Kazeen; Bhat, Deepa; Fish, Jason; Halm, Ethan A.
Background: Although elevated glucose values are strongly associated with undiagnosed diabetes, they are frequently overlooked. Patient, provider, and system factors associated with failure to follow-up elevated glucose values in electronic medical records (EMRs) are not well described. Methods: We conducted a chart review in a comprehensive EMR with a patient portal and results management features. Established primary care patients with no known diagnosis of diabetes and ≥ 1 glucose value >125 mg/dL were included. Follow-up failure was defined as (1) no documented comment on the glucose value or result communication to the patient within 30 days or (2) no hemoglobin A1c (HbA1c ) ordered within 30 days or resulted within 12 months. Associations were examined using Wilcoxon and χ 2 tests. Results: Of 150 charts reviewed, 97 met inclusion criteria. The median glucose was 133 mg/dL, and 20% of patients had multiple values >125 mg/dL. Only 36% of elevated glucose values were followed up. No associations were observed between patient characteristics, diabetes risk factors, or provider characteristics and follow-up failures. Automated flagging of glucose values ≥140 mg/dL by highlighting them red in the EMR was not associated with improved follow-up (46% vs 32%; P = .19). Even when follow-up occurred (n = 35), only 31% completed gold standard diabetes testing (HbA1c ) within 12 months. Of the resulted HbA1c tests (n = 11), 55% were in the prediabetes range (5.7%-6.4%). Conclusions: Two-thirds of elevated glucose values were not followed up, despite EMR features facilitating results management. Greater understanding of the results management process and improved EMR functionalities to support results management are needed.